“Taqwim al-Buldan” by Abu al-Fida as a Source on Medieval Geography of Khwarazm and Transoxiana - Zhuzbayeva, Uldanay; Zhanakova, Nurgul; Noyanov, Yedil; Sailan, Bolat; Arynov, Zhumakan (Journal of Al-Tamaddun, 2025)
A detailed study of the work of Abu al-Fida “Taqwim al-Buldan” will make it possible to better understand the peculiarities of the Central Asian region at that time, which determines the relevance of this research. The purpose of the article is to study and analyse the data on Khwarazm and Transoxiana in the work “Taqwim al-Buldan”. Various methods were used in the study: historical-critical, comparative, descriptive, critical analysis method, content analysis method, discourse analysis method. In the course of the research, it was concluded that Abu al-Fida gives a list of 7 cities and villages in the description of Khwarazm as well as 42 settlements in Transoxiana. In his description, Abu al-Fida pays special attention to gardens, minerals, fortifications, cathedral mosques, as well as the state of science in cities. Speaking about the population of Khwarazm and Transoxiana, Abu al-Fida pays attention to the religion of the inhabitants of these cities. He identifies Mongols, who at that time controlled Central Asia, as non-Muslims, expressing a certain regret that the cities of Central Asia, which were dominated by Muslims, are now dominated by pagans. The practical significance of the article lies in the fact that the introduction into scientific circulation of the study of data on Khwarazm and Transoxiana in the work “Taqwim al-Buldan” will allow better understanding the medieval Islamic scholars of the Central Asian region, and, in this regard, the article can be used for further research of this problem.